Protecting adults at risk of pneumococcal infection and influenza from exposure to SARS-CoV-2 - Edwin David George McIntosh; K. Feemster; J. Rello (Taylor & Francis Group, 2022)
There is a paucity of evidence linking pneumococcal infection and influenza with SARS-CoV-2 and COVID-19. There is circumstantial evidence of the possibility of an association between S. pneumoniae and SARS-CoV-2 such as the increased binding of S. pneumoniae to coronavirus-infected human airway epithelium, the frequent use of broad-spectrum antibiotics in the management of COVID-19 which could mask secondary bacterial infection, and the observation that pneumococcal vaccination is associated with decreased SARS-CoV-2 nasopharyngeal swab positivity. We performed a targeted literature review for the year 2020, using search terms S. pneumoniae, influenza, SARS-CoV-2, and found 25 relevant articles of a total of 291. Pneumococcal and influenza vaccinations have the potential to contribute toward efforts aimed at reducing the health burden of SARS-CoV-2, especially by reducing preventable admissions to hospital for pneumonia and the consequent risk of nosocomial SARS-CoV-2 transmission.